The Effect of Aerobic Exercise on Blood Glucose Levels in Type 2 Diabetes Mellitus Patients: Critical Review - Farid Rahman; Muhammad Irfan Setiadi; Ilham Setya Budi; Ardianto Kurniawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Aerobic exercise is a systematic exercise activity with a gradual and continuous increase in load that uses energy derived from combustion using oxygen, and requires oxygen without causing fatigue. The purpose of this study was to determine whether there is an effect of aerobic exercise on reducing blood glucose in patients with diabetes mellitus type 2. The design and research method carried out in this study used a critical review system. unbalanced, and low physical activity, due to low physical activity, it is necessary to exercise so that physical activity can be maintained, namely aerobic exercise. Based on the results of studies that have been conducted on the effect of aerobic exercise on reducing blood glucose levels in patients with diabetes mellitus type 2, it can be concluded that the dose of moderate intensity aerobic exercise is optimal in reducing blood sugar levels in patients with diabetes mellitus type 2.